(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
This paper describes the cases filed at the Public Ministry’s Victims Assistance Center in Ñeembucu. Child molestation is a type of abuse that has been encreasing over time. Its visibility was given progressively thanks to the approval of national and international acts that protect childhood. Statistics show the worldwide existence of child molestation. This study’s main objective is to know the quantity of child molestation cases that were filed at the Victims Assistance Center in Ñeembucu, and also to describe its incidence and prevalence in the last five years. The metodology adopts a descriptive quantitative approach, by using the request forms that were filed at the criminal units in the Department of Ñeembucu, and also the interview worksheets. Through the documentary review it could be determined the prevalence in child molestation cases, besides that, the results enabled to quantify and clasify the analysed population according to variables such as: age, sex, and Department’s districts; and also to identify the incidence of cases filed at the Victims Assistance Center, with steady increase in the last five years.